Pengaruh Variasi Konsentrasi H2SO4 Dan Waktu Hidrolisis Dalam Pembuatan Glukosa Dari Bungkil Inti Sawit (BIS) - Tri Lusi Lisa Dila; Silvia Reni Yenti; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Indonesia is the largest producer of crude palm oil (CPO), followed by Malaysia and Thailand. The area of Indonesian palm oil plantations produces palm kernel oil (PKO) and palm kernel cake (PKC) 8,573,886 tons / year. BIS has lignocellulose content, lignocellulosic structure can be converted to glucose and has the potential to become bioethanol which can meet Indonesia's energy needs. The objectives to be achieved in this research are to characterize PKC as a raw material and determine the best H2SO4 concentration and hydrolysis time in the manufacture of glucose. There are two stages in this research, namely delignification and hydrolysis. Delignification uses a base solvent with a concentration of 6% NaOH cooking process at a temperature of 100 oC and a reaction time of 1 hour. The results showed that the base treatment process was able to increase cellulose to 39.1%, hemicellulose 10.9%, and a reduction in lignin by 5.65%. Second, hydrolyzed using variations of H2SO4 (1, 2 and 3 M) and hydrolysis time (3, 4 and 5 hours) at a temperature of 100 oC. The highest sugar concentration was produced from the hydrolysis process at a concentration of H2SO4 3 M and a 5 hour hydrolysis time of 22.11 g / L. Keywords: glucose, hydrolysis, palm kernel cake